NANOENCAPSULATION OF LEMONGRASS OIL AS A NOVEL STRATEGY TO COMBAT ANTIMICROBIAL RESISTANCE (Applied Biological Research, 2026)
The increasing prevalence of multidrug-resistant (MDR) bacteria has necessitated to formulate alternative antimicrobial strategies. This study evaluated the antibacterial efficacy of lemongrass oil (LGO) nanoencapsulated in chitosan nanoparticles against MDR Staphylococcus aureus (MDRSA) and Escherichia coli (MDREC). Ionic gelation technique was used to synthesise lemongrass oil loaded chitosan nanoparticles which were further characterized by dynamic light scattering (DLS), field emission scanning electron microscopy (FESEM), UV-Visible spectrophotometry, and FTIR analysis. A significant increase in particle size from 168.7 nm for plain chitosan nanoparticles to 318.7 nm following LGO encapsulation, with acceptable polydispersity was observed through DLS, while FESEM confirmed spherical nanoparticles with smooth surfaces and sizes ranging from 50 to 150 nm. Encapsulation efficiency and loading capacity range was 41.7-91.17 and 21.36-74.36%, respectively, with maximum values observed at a 1:1 chitosan-to-LGO ratio. Nanoencapsulation significantly enhanced the antibacterial activity, with LGO-loaded nanoparticles exhibiting lower MIC values as compared to the free LGO against MDRSA (0.052% vs 0.125%) and MDREC (0.0104% vs 0.25%). Similarly, reduced MBC values were observed for the nanoformulation. These findings demonstrate that chitosan-based nanoencapsulation significantly improves the antibacterial efficacy of lemongrass oil against MDR pathogens.
Keywords: Antibacterial activity, characterization, lemongrass oil, multidrug resistant, nanoencapsulation